PENERAPAN MODEL PEMBELAJARAN INKUIRI DENGAN MENGGUNAKAN INDEX CARD MATCH (ICM) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMA N 7 MERANGIN TAHUN PELAJARAN 2019/2020 - Eva Afkalorin; Rodiantifitri Nengsih; Andriyanto Andriyanto (BIOCOLONY, 2019)
This research is motivated by the low learning outcomes of Biology students of class X SMA Negeri 7 Merangin in teaching and learning activities of students less active in the learning process, the learning strategies used by teachers are still less variable. The purpose of the study was to improve Biology Learning Outcomes of students of Class X sMA Negeri 7 Merangin 2019/2020 Learning Year on Biodiversity material by Application of Inquiry Learning Model using Index Card Match (ICM). The design of this research is Research Classroom action (PTK) carried out in class X SMA Negeri 7 in the 2019/2020 Academic Year with a total of 17 students consisting of 8 male students 9 female students. Data were collected using written test techniques and observation of students during the process learning takes place. The results of this study are found that the results of Biology learning in Grade X students of State 7 in the year of 2019/2020 Learning Year increased. The increase can be seen from the acquisition of the average value of learning outcomes with a percentage of 65% cycle I and increasing in cycle II with a percentage of 82% thus it can be concluded that the application of the Inquiry Learning model using Index Card Match (ICM) can improve learning outcomes Biology Students of class X SMA Negeri 7 celebrate 2019/2020 Academic Year.